Edukasi dan Aksi Gizi untuk Meningkatkan Kualitas Kesehatan Peserta Didik di SD Negeri Mengok 2 - Laili, Anneja Maghfirotul; Wardani, Amanda Julia; Saindra, Rafi Dzulfiqar Faiz; Oktavia Rahma; Prakoso, Bhim; Nasir, M. Abd.; Qori’ah, Ciplis Gema; Wardhono, Adhitya; Syahzanan, Fatimah; Nisah, Ulfatun; Nawu, Maria Natalia; Puspito, Agung Nugroho (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Education is a learning that aims to enable each individual to develop their potential. For the ideal age, nutrition education should be provided to children when they reach the age of 6 to 14 years. This research is motivated by the lack of student knowledge about nutrition. Teachers only provide the material that is taught but the application is limited. The solution to this problem is to provide additional material for students at SD Negeri Mengok 2 and how to implement it properly and correctly. The purpose of this study is to find out the development that has been undergone by students when we provide nutrition education. This research uses conventional methods by involving lectures, practice, and technical assistance to students. The instruments used are in the form of student activity observation sheets and using tests. The data analysis technique used is quantitative. The results of the study showed an increase in students' response and understanding of the education we provided.